Modeling reveals the role of coastal upwelling and hydrologic inputs on biologically distinct water exchanges in a Great Lakes estuary. (30th September 2018) - Liu, Qianqian; Anderson, Eric J.; Zhang, Yinglong; Weinke, Anthony D.; Knapp, Katie L.; Biddanda, Bopaiah A.
Abstract: Freshwater estuaries everywhere are under stress from anthropogenic activities and climate change. Muskegon Lake Estuary (MLE) is a freshwater estuary along the eastern shore of Lake Michigan characterized by algal blooms and hypoxia during the summer and designated as an Area of Concern (AOC) by the EPA. We developed a 3-D hydrodynamic model using the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM) to study the hydrodynamics of MLE with a focus on the cold-water intrusions from Lake Michigan into MLE. Substantial water exchange process was validated by comparisons with observations in the near-shore region of Lake Michigan and in the navigation channel between Lake Michigan and MLE. The model found that the cold-water intrusions from Lake Michigan to MLE occur during summer stratification, amounting to as much as 10% of MLE's total volume during one single episodic event. The intrusion was accompanied by a stronger surface outflow in the opposite direction, which may accelerate the delivery of MLE water to Lake Michigan. Through process-oriented model experiments, we examined the cold-water intrusion's responses to hydrological shift under climate change, and found that the increase in riverine input during upwelling weakens the intrusion. In addition, an increase of navigation channel width strengthens the cold-water intrusion, and that intrusion strength as well as intrusion period was directly related to wind speed. Our observation-modeling based findings would provide a good reference for the future study of biophysical interactions between coastal ocean and estuaries. Highlights: A hydrodynamic model was developed for a freshwater estuary and the offshore coastal region. Cold-water intrusions from the Great Lakes to an estuary during upwelling events were studied. The cold-water intrusion mitigates hypoxia in the estuary and accelerates water exchange. Climatic hydrologic shift, navigation channel width and wind speed modulate the intrusion. Hydrodynamics in this freshwater estuary serves as a model microcosm for other similar coastal estuaries.